Scientific Approach and Spirituality in Islamic Economic Development: A Philosophical Analysis of Science - Ramlah Ramlah; Abdul Wahab; Muhammad Wahyuddin Abdullah; Sunarto Natsir (Insitut Muslim Cendekia, 2025)
This study aims to provide both a concise and in-depth discussion of the science approach within the context of Islamic economics. Using a qualitative method based on library research, this study examines recent academic literature to identify research gaps and propose novelty in the construction of Islamic economic epistemology. The findings indicate that the epistemology of Islamic economics is grounded in divine revelation (the Qur’an and Sunnah), integrated with reason and empirical reality; its ontology emphasizes that economic activities are acts of worship and a trust to prosper the earth; while its axiology is oriented toward falah (worldly and eternal well-being), justice, maslahah (public interest), and sustainability. These findings reveal that Islamic economics is tauhidi (monotheistic), integrative, and transformative, serving not only as an alternative but also as a conceptual and practical solution to contemporary socio-economic challenges. The implementation of Islamic instruments such as productive zakat, waqf, and green sukuk demonstrates the practical relevance of Islamic economics in establishing a just, inclusive, and sustainable system.